The significance of BRAF V600E mutation status discordance between primary cutaneous melanoma and brain metastases: The implications for BRAF inhibitor therapy. Issue 48 (December 2017) - Hannan, Enda J.; O'Leary, Donal P.; MacNally, Stephen P.; Kay, Elaine W.; Farrell, Michael A.; Morris, Patrick G.; Power, Colm P.; Hill, Arnold D.K.
Abstract : Abstract: To compare BRAF V600E status of primary melanoma and brain metastases to assess for discordance by cross-sectional study, and to evaluate clinical implications on BRAF inhibitor therapy. Brain metastases are common in patients with advanced melanoma. Between 40% and 60% of melanomas demonstrate BRAF mutations, BRAF V600E being most common. Selective BRAF inhibitor therapy has shown improvement in outcome in patients with melanoma. It has been demonstrated that not all metastatic lesions carry the same BRAF mutation status as the primary, but the frequency in which discordance occurs remains unclear. Establishing this may have implications in the use of BRAF inhibitors in patients with melanoma brain metastases. Patients who underwent metastectomy for melanoma brain metastases were identified using our local histopathology database. A review of histology of the primary lesion and the metastasis was performed for each patient, assessing for BRAF mutation status discordance. Fourty-two patients who underwent a brain metastectomy following excision of a melanoma primary were identified over a 7-year period. Median survival was 9 months. The median Breslow thickness for the primary lesion was 3.4 mm. Six patients (14%) had discrepancy between the BRAF status of a melanoma primary and metastatic lesion. Of these 6 patients, 3 had a BRAF mutation positive primary with a BRAF mutation negative metastatic lesion, while the other 3 had a BRAF mutation negative primary with BRAF mutation positive metastasis. There is an important discordance rate in the BRAF mutation status of melanoma primaries versus brain metastases.